Facing an uncomfortable theme: Public policies and the provision of public services for legal interruption of pregnancy in Brazil (Research, Society and Development, 2022)
This article aims to promote the examination of public health policies for women within the scope of the Unified Health System (SUS), focusing on public policies, services, programs, and projects around the legal termination of pregnancy in Brazil, the so-called Legal Abortion. As a methodology, a bibliographic review is used, as well as documentary research on the quantitative of public policies around the legal interruption of abortion, based on a quantitative-qualitative approach and exploratory objectives, using the hypothetical-deductive method, considering the need to reinterpret the data obtained from a theoretical debate that relates violence against women, reproductive rights, and state responsibility. With the analysis of statistical data, it is clear that there is still a great disharmony between what is foreseen in the Brazilian legal system and, especially, in the formation and regulation of public health policies and the reality of adequate and concrete provision of care services to health of women undergoing legal abortion. The respect and guarantee of the rights stipulated in the recommendations, ordinances and technical standards is, therefore, fortuitous, and insufficient. The results indicate that the state's ineffectiveness regarding the constitutional guarantee of this right produces even more gender injustice in the country. In short, it is necessary for the State to assume the commitment to carry out existing public norms and policies, trying to improve, expand, develop, and consolidate policies, programs and integrated and intersectional actions that involve women's health in the face of the problem of abortion.